Systemic Inflammation in Pregnant Women With Periodontitis and Preterm Prelabor Rupture of Membranes: A Prospective Case-Control Study - Mohr, Stefan; Amylidi-Mohr, Sofia K.; Stadelmann, Pascale; Sculean, Anton; Persson, Rutger; Eick, Sigrun; Surbek, Daniel V. (Frontiers in Immunology, 2019)
AIMS Periodontal disease is associated with adverse pregnancy outcome (APO), but the underlying pathophysiologic mechanism is still unknown. In this prospective, longitudinal, non-interventional case-control study, 45 women with PPROM and 26 controls with uncomplicated pregnancies were examined at three time-points (T1: 20-34 weeks of gestations; T2: within 48h after delivery; T3: 4-6 weeks post partum). Examinations included subgingival, blood, vaginal, and placenta sampling for microbiologic, cytokine and histology assessment. Objective of this study was to test the hypothesis that systemic inflammatory changes and not specific bacteria are predominantly involved in the association between periodontal disease and APO. RESULTS Demographic data and gestational age at T1 were comparable between groups. While there was no correlation between vaginal and gingival fluid microbiome, cytokine levels in the assessed compartments differed between cases and controls. Vaginal smears did not show a higher rate of abnormal flora in the cases at the onset of PPROM. Number and variety of bacteria in the case group placental membranes and vagina were higher, but these bacteria were not found in membranes at birth. CONCLUSIONS On the basis of our results we speculate that an inflammatory pathway sequentially involving periodontal tissue, maternal serum and finally vaginal compartment contributes to the underlying pathomechanism involved in PPROM associated with periodontitis.